The Dutch public are positive about the colorectal cancer-screening programme, but is this a well-informed opinion? - Linda N. Douma; Ellen Uiters; Danielle R. M. Timmermans (BMC, 2016)
Abstract Background Population-based colorectal cancer (CRC) screening is widely recommended, and members of the eligible screening population seem to be positive about it. However, it is not well known how people outside the eligible screening population view CRC screening, and whether they are supportive of the government providing this. Public opinion may affect people's personal views and their screening decision. The aim of our study was to examine the opinion of the Dutch general public regarding the national CRC screening programme. Method An online survey was carried out in a Dutch population sample of adults aged 18 and older, assessing level of support, personal attitude, collective attitude, perceived social norm, awareness, and knowledge regarding the CRC screening programme. Results The response rate was 56% (n = 1679/3000). Generally, the Dutch public are positive about and supportive of the CRC screening programme. We found the biggest proportion of support (86%) when people were asked directly. A smaller proportion (48%) was supportive when people had to choose between other options concerning how the government could possibly deal with CRC. People report knowing more about the benefits of CRC screening than about its possible harms and risks. Many people found it difficult to answer the knowledge questions that asked about numerical information concerning CRC screening correctly. Conclusion People were less supportive of the CRC screening programme when having to choose between other options concerning dealing with CRC, and their support may not be based on a full comprehension of what CRC screening entails. Further research is needed to establish what knowledge people need in order to form a well-founded opinion.